Analysis Of The Brazilian Mineral Production And Technical Responsables Based On Ral Access - Gabriel Rubio Pirillo; Maurício Guimarães Bergerman; Humberto Almeida de La Serna; Kayleigh Meneghini (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The Mining Annual Report (RAL) is an obligation for every current owner of a brazilian mining process which is already undergoing extraction. This document is basically composed by the company’s annual book balance, where is possible to educe informations that allow to evaluate the mineral market behavior. This research gathered filtered data linked with RAL production and technical responsability between 2010 and 2017, gotten by the Information Access Law, without the real CNPJ of each company, in order to preserve their identity. The results allow to quantify the Brazilian mining production during the period, illustrating that approximately 46% of the companies can be classified as micro, 30% as small, 20% as medium and 4% as large mining companies. It was observed that the micros concentrate the most part of technical responsibles who sign for more than three mines.